Analisis Kesalahan Mahasiswa pada Penyelesaian Soal Mata Kuliah Anatomi & Fisiologi Manusia - Miswandi Tendrita (Magister Pendidikan Biologi, Universitas Negeri Medan, 2020)
Human Anatomy and Physiology is one of the courses for biology students that is abstract so that not a few students have difficulty studying it. Errors in answering questions can be used as clues to determine the student's mastery of material. This study aims to determine student errors in solving problems in the Human Anatomy & Physiology course. This research is a qualitative descriptive study. The data collection method used is the test method. The subjects in this study were biology education students in semester V of the Nineteenth November University Kolaka Academic Year 2019/2020 who took Human Anatomy and Physiology courses. The instrument used in this study was the UAS test questions in the Human Anatomy & Physiology course. The results of the analysis showed that the most difficult questions for students to understand were questions on the function of the eye parts where the points obtained by nine students were only 2 points with the percentage of correct answers only 2%. While the questions on autoimmune disease material got the most correct percentage of answers where the number of points was nine students, namely 31 with a percentage of 34%. From the research results, it can be concluded that by analyzing student errors in answering questions, it can be seen what material is difficult for students to understand so that it can help lecturers to improve the learning process in the following semester.